TUNTUTAN KOMPETENSI GURU PROFESIONAL BAHASA INDONESIA DALAM MENGHADAPI ABAD 21 - Subyantoro Subyantoro; Suhud Aryana; Rahayu Pristiwati (STKIP Siliwangi, 2022)
Today's teachers are not only fixated on their professional competencies, but in the 21st century a teacher gets demands for additional competencies based on technology, critical thinking, creative and innovative. This research aims to describe some of the demands for the competence of a professional Indonesian teacher in facing the 21st century. This type of research is a qualitative descriptive with the Systemic Literature Review method as steps to describe the competence of a professional Indonesian teacher in the 21st century. Data collection is carried out through secondary data, namely a study the theory and the results of previous studies that have been carried out by researchers through access to google schooler, google trend, google maps, publish or perish. The data collection analysis technique in this study was through the steps of describing, comparing, and evaluating or describing. findings. The results show that the demands for the competence of Indonesian language professional teachers do not have to be fixed in 4 components such as pedagogical, professional, personality and social but also must have additional Technological Pedogical Content Knowledge (TPACK), Critical Thinking, Communication, Collaboration, Creativity and Innovation (TPACK) skills. 4C), Higher Order Thinking Skills (HOTs), Massive Open Online Courses (MOOCs) and digital literacy.